Acute-onset psychosis induced by a therapeutic dose of parenteral hyoscine butylbromide: A case report (Indian Journal of Case Reports, 2024)
Anticholinergic medications are frequently prescribed for gastrointestinal and genitourinary spasms. Psychosis, when present, results from anticholinergic overdose or toxicity. In the literature, anticholinergic-induced psychosis at therapeutic doses in patients with normal cognition is extremely uncommon. Here, we describe the case of a 28-year-old female who presented with auditory and visual hallucinations, stereotypy, and agitation after receiving a single intramuscular injection of 20 mg hyoscine butylbromide for dysmenorrhea. Even though it is rare for a therapeutic dose of hyoscine butylbromide to cause psychosis, clinicians should maintain a high index of suspicion and be cautious when administering or prescribing anticholinergics.